2017
DOI: 10.1136/bmjopen-2017-017761
|View full text |Cite
|
Sign up to set email alerts
|

Sharp instrument injuries among hospital healthcare workers in mainland China: a cross-sectional study

Abstract: ObjectivesTo determine the prevalence of sharp instrument injuries in hospital-based healthcare workers (HCWs) in mainland China and the contributing factors.DesignCross-sectional study.SettingThe data were derived from public hospitals.ParticipantsA total of 360 hospitals were recruited in the study, including 289 general hospitals and 71 specialised hospitals. Among them, 194 are tertiary-level hospitals and 166 are secondary level. The study population finally consisted of 223 149 hospital HCWs.Primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
5
17
1
Order By: Relevance
“…In the present survey, 16.0% of nurses reported experiencing at least one insulin-injection-related NSI, which is lower than the rates found by Zhao et al [16] (39.1%), Dong et al [8] (19.33%), and Costigliola et al [9] (32%). Two large-scale surveys in China found that the overall incidence rates of NSIs among nurses were 7.8% [17] and 10.3% [17,18], which are lower than the rate found in this study. These discrepancies in the incidence of NSIs among different studies may be related to factors such as the included hospitals and countries [19]; however, overall the results of the various studies show that there is a relatively high incidence of NSIs caused by insulin injection among clinical nurses [20].…”
Section: Analysis Of the Occurrence Of And Risk Factors For Insulin-injection-related Nsiscontrasting
confidence: 93%
See 1 more Smart Citation
“…In the present survey, 16.0% of nurses reported experiencing at least one insulin-injection-related NSI, which is lower than the rates found by Zhao et al [16] (39.1%), Dong et al [8] (19.33%), and Costigliola et al [9] (32%). Two large-scale surveys in China found that the overall incidence rates of NSIs among nurses were 7.8% [17] and 10.3% [17,18], which are lower than the rate found in this study. These discrepancies in the incidence of NSIs among different studies may be related to factors such as the included hospitals and countries [19]; however, overall the results of the various studies show that there is a relatively high incidence of NSIs caused by insulin injection among clinical nurses [20].…”
Section: Analysis Of the Occurrence Of And Risk Factors For Insulin-injection-related Nsiscontrasting
confidence: 93%
“…In the present study, 75% of the devices had been contaminated when an insulin-injection-related NSI occurred, which is similar to the findings of previous NSI surveys conducted in Korea [33] (60.6%) and China [18] (77.5%). More than two-thirds of insulin-injection-related NSIs experienced by clinical nurses involved contaminated sharps.…”
Section: What Happens When a Nsi Occurssupporting
confidence: 90%
“…The majority of the injuries were largely due to hollowbore needle injuries (66.7%), mainly disposable syringes (45.5%), which is consistent with the results of many previous studies. 14 20 23 25 Recapping practices resulted in some NSSIs in our study. Due to limited resources at the hospital, safety-engineered devices (SEDs) were rarely used.…”
Section: Discussionmentioning
confidence: 73%
“…In recent decades, occupational exposure among healthcare workers (HCWs) has increased. HCWs are frequently exposed to medical sharp instruments (Huang et al, 2017). Needle stick injuries (NSIs) are one of the most common hazards for HCWs, particularly nurses (Tawil, 2016).…”
Section: Introductionmentioning
confidence: 99%